Teachers’ and Students’ Perspectives on English-Javanese Code-Switching in the Classroom - Hilya; Haryanto (Universitas Pendidikan Ganesha, 2025)
Code-switching and code mixing are common phenomena in multilingual educational contexts, particularly in English as a Foreign Language classrooms. These practices are often employed as pedagogical strategies to address students’ limited language proficiency; however, their effectiveness requires further empirical investigation. This study aims to analyze the types and functions of code switching used in classroom interaction and to explore teachers’ and students’ perspectives on its use in learning. Adopting a qualitative approach, this study involved 30 eleventh grade students and one English teacher. Data were collected through classroom documentation and semi structured interviews, then analyzed by identifying and classifying instances of code switching based on Naibaho’s classification and the functional framework proposed by Mattson and Burenhult. The findings reveal that inter sentential switching was the most dominant type of code switching at 66%, while the repetitive function emerged most frequently at 48%. These findings indicate that code switching is aligned with teachers’ pedagogical purposes in clarifying meaning and enhancing students’ comprehension. Both teachers and students expressed positive attitudes toward the use of code switching, including the potential use of English-Javanese code switching to support classroom interaction and understanding. This study concludes that code-switching serves as an effective pedagogical strategy in facilitating comprehension, interaction, and language learning in multilingual classrooms and implies the need for its planned and proportional use as part of English teaching practices.